Social Mobility in the 20th Century : Class Mobility and Occupational Change in the United States and Germany - Hertel, Florian R. (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
Based on a novel class scheme and a unique compilation of German and American data, this book reveals that intergenerational class mobility increased over most of the past century. While country differences in intergenerational mobility are surprisingly small, gender, regional, racial and ethnic differences were initially large but declined over time. At the end of the 20th century, however, mobility prospects turned to the worse in both countries. In light of these findings, the book develops a narrative account of historical socio-political developments that are likely to have driven the basic resemblances across countries but also account for the initial decline and the more recent increase in intergenerational inequality. Contents Development of an historical account to explain change in social mobility Critical review of the main conceptualizations of social stratification Conceptualization, test and application of a new class scheme In-depth analysis of absolute and relative mobility in Germany and the U.S. Comparison of social mobility chances in the U.S. and Germany Target Groups Scholars and students of class analysis, social mobility and social inequality research Social policy developers aiming at understanding the reproduction of social inequality< The Author Florian R. Hertel is Max Weber Fellow at the European University Institute in Florence. He is working on issues of stratification, inequality and intergenerational mobility in European countries and the U.S.
Keywords: Social sciences.; Social structure.; Social inequality.; Industrial sociology.; Demography.; elektronické knihy; electronic books